An Evaluation of the Third Year Primary School Text-Book “My Book of English - ANTRI Chaima (My University, 2024)
Abstract The study aims at investigating the effectiveness, authenticity and suitability of the text-book of third year primary school “My Book of English”. For testing the hypotheses which suggest that the text-book is suitable and effective for the learners and that the attitude of English as Foreign Language (EFL) teachers toward it is positive, the researcher used and depended on a checklist as the main tool to evaluate the text-book; and a questionnaire designed to teachers. The participants have been chosen randomly to review the attitude of each one. The probable significance of this study is to present a valuable result for syllabus designers, textbooks writers and teachers for better notions in the future. ------------------- الملخص تهدف الدراسة إلى التعرف على مدى فاعلية وأصالة وملاءمة الكتاب المدرسي للصف الثالث الابتدائي "كتابي في اللغة الإنجليزية". ولاختبار الفرضيات التي تشير إلى أن الكتاب المدرسي مناسب وفعال للمتعلمين وأن اتجاهاتهم نحوه إيجابية، استخدم الباحث واعتمد على قائمة المراجعة كأداة رئيسية لتقييم الكتاب المدرسي؛ واستبيان للمعلمين. تم اختيار المشاركين بشكل عشوائي لمراجعة موقف كل منهم. تكمن الأهمية المحتملة لهذه الدراسة في تقديم نتائج قيمة لمصممي المناهج ومؤلفي الكتب المدرسية والمعلمين من أجل مفاهيم أفضل في المستقبل -------------------- Résume L'étude vise à étudier l'efficacité, l'authenticité et l'adéquation du manuel de troisième année de l'école primaire « My Book of English ». Pour tester les hypothèses suggérant que le manuel est adapté et efficace pour les apprenants et que leur attitude à son égard est positive, le chercheur a utilisé et s'est appuyé sur une liste de contrôle comme principal outil d'évaluation du manuel ; et un questionnaire pour les enseignants. Les participants ont été choisis au hasard pour revoir l'attitude de chacun. L'importance probable de cette étude est de présenter des résultats précieux pour les concepteurs de programmes, les rédacteurs de manuels scolaires et les enseignants pour de meilleures notions à l'avenir